Stanmat: um jogo exclusivo para deficientes visuais - Carvalho, Camila Perim de (Universidade Federal Rural do Semi-Árido, 2019)
Currently, there is still a shortage of games for the visually impaired and those that are proposed are very simple, consisting basically of sound, with no graphic interface, which does not contribute to the social inclusion of the visually impaired. As noted in the literature, people with visual impairment present greater difficulty in the discipline of mathematics, because most of the content of this subject needs visual resources to be understood. Faced with this problem, this work proposes an inclusive game for teaching-learning of the four basic operations of mathematics, aiming to provide efficient environments for both social inclusion and educational development of people with visual impairment. The construction of this work was based on diaries of borders, originating from the workshops held in the Association of Parents and Friends of the Exceptional (APAE) of Pau dos Ferros. Studies were carried out on visual impairment, digital games, inclusive games, serious games and adaptive and sonic techniques, with the purpose of building ideas, knowledge and knowledge to serve as a basis for the development of the proposed game. As a result of this work, we have the "StanMat", a game that follows the perspective of serious games, that is, that seek to impart knowledge or skill to the player.
Monografia
Keywords: Jogos digitais; Deficiência visual; Jogos inclusivos; Digital games; Visual impairment; Inclusive games; CIENCIAS EXATAS E DA TERRA::TECNOLOGIA DA INFORMACAO